A Damage Constitutive Model of Red Sandstone under Coupling of Wet-Dry Cycles and Impact Load - Bin Du; Haibo Bai (Shock and Vibration)
In the engineering fields of mining, tunneling, slopes, and dams, rocks are usually subject to the coupling effect of impact load and wet-dry cycles. The deformation rule of rocks under the coupling effects is a symbolic mechanical property, which lays the foundation for the design and evaluation in the rock engineering. In this paper, the coupling damage was classified as mesodamage induced by wet-dry cycles and macrodamage induced by impact load, and the loading rate effect was considered as the load damage. Besides, a constitutive model of coupling damage was concluded based on Lemaitre’s strain equivalent assumption. Consequently, the validity of the model was verified by a series of dynamic compression tests of red sandstone. Results indicated that the proposed damage constitutive model can definitely describe the dynamic stress-strain curves of red sandstone after wet-dry cycles and impact load. The evolution of coupling damage curves showed that wet-dry cycle damage plays a dominant role in the elastic deformation stage, while the yield failure stage is controlled by the load damage in which the loading rate cannot be ignored. Parametric study was also performed to analyze the effect of parameters on dynamic stress-strain curves. The proposed mode has the simple and reliable operation with few parameters and can efficiently predict the long-term deformation behavior of rocks subject to multiple wet-dry cycles.